Nations in Commemoration: Theory, Historiography and Studies of the Latin American Patriotic Bi-Centennials, 20th-21st Centuries - Ortemberg, Pablo (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
This article is structured in three parts. The first is devoted to the theory and conceptualization of the commemorations of the political community in general, highlighting the interdisciplinary nature of the object. The second part reviews the perspectives adopted in research on the patriotic centennials in Latin America during the first wave around 1910 and the second wave of the 1920s. The final part deals with the recent past, presenting a balance -necessarily provisional- of the studies on the commemorations of the Bicentennials around the year 2010 and the second wave of celebrations currently underway. The texts identifies transversal issues across the two historical moments, weighs the specificities and emphases in each agenda (including the types of sources available), along with questions and approaches that are still pending to be explored in more depth in each case, especially those arising in the current commemorations: the relationship between memorial struggles and dynamics of inclusion-exclusion in the representations of the nation; the comparative and connected analyses at the international and subnational levels, and the use of ethnographic tools for the study of the public spheres.
Keywords: centennials; bicentennials; Latin America; theory; historiography